The relationship between religious coping, shame- proneness, guilt- proneness and expressed emotion among family members of individuals with chronic mental disorder - حمید خانی پور; حکیمه تاراسی; ابوالفضل حاتمی; مهدی اکبری (فصلنامه خانواده پژوهی, 2019)
Expressed emotion has been considered as one of the main predictors of relapse among individuals with chronic mental disorders. The aims of this study were (1) to investigate the association between expressed emotion, religious copings and shame- proneness, guilt- proneness among family members of people with chronic mental disorders, and (2) examining the differential relationship between shame- proneness, guilt- proneness and religious copings. Sample (n=116) which was selected by convenient method were people who had an individual with mental disorders in their families and who were supported by Iranian welfare organization. Participants were asked to filled demographic checklist, brief religious coping scale, test of self-conscious affect, and family questionnaire. Multiple regression analysis indicated that positive religious coping could predict expressed emotion above and beyond other variable. Furthermore, shame-proneness was directly associated with negative religious coping and inversely associated with positive religious coping. Also, guilt-proneness directly correlated with positive religious coping and inversely correlated with negative religious coping. It seemed positive religious coping could be a protective factor for expressed emotion in families with members whom had mental disorder. Individual traits like shame proneness and guilt proneness would not predict expressed emotion and this may have indicated the likely importance of social stigma against mental disorders. Differential relationship between shame proneness and guilt proneness with religious copings revealed that shame-proneness would be related to developing negative religious coping, whereas guilt-proneness may be considered as a contributing factor for developing positive religious coping.